Employing capital: Patient capital and labour relations in Kenya's manufacturing sector - Florence Dafe; Radha Upadhyaya; Christoph Sommer (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Generating decent employment is key to the creation of a new social contract and social cohesion in Sub-Saharan Africa. The crucial question is, thus, how can more decent jobs be created? Much of the extant research has focused on the role of states and businesses in shaping employment relations. In this paper, we draw attention to a third type of actor that has been largely absent in the literature on the determinants of employment relations in developing countries: financial institutions. Based on data from 38 interviews of Kenyan manufacturing firms, financiers and labour representatives before and during the COVID19 pandemic, we examine the relationship between the patience of capital and labour relations. In particular, the evidence presented in this paper suggests that access to more patient sources of capital may help to enhance the quantity and quality of jobs in African countries. We discuss three mechanisms through which this occurs. Our paper contributes to the growing body of research on patient capital (which largely focuses on developed countries) by extending it to the context of lower income African countries; it also speaks to the broader debates about how to enhance the contribution of finance capital to social cohesion.
Keywords: 330